Interleukins: Pathogenesis in Non-Alcoholic Fatty Liver Disease - Saira Rafaqat; Sanja Gluscevic; Filiz Mercantepe; Sana Rafaqat; Aleksandra Klisic (Metabolites, 2024)
Inflammatory cytokines have been implicated as crucial contributors to the onset and progression of non-alcoholic fatty liver disease (NAFLD). The exact mechanisms by which interleukins (ILs) contribute to NAFLD may vary, and ongoing research is aimed at understanding the specific roles of different ILs in the pathogenesis of this condition. In addition, variations in environmental factors and genetics in each individual can influence the onset and/or progression of NAFLD. The lack of clinical studies related to the potential therapeutic properties of IL-1 inhibitors currently does not allow us to conclude their validity as a therapeutic option, although preclinical studies show promising results. Further studies are needed to elucidate their beneficial properties in NAFLD treatment.